Monitoring Poverty Trends in Ireland 2004-2007: Key Issues for Children, People of Working Age and Older People - RUSSELL, HELEN; MAITRE, BERTRAND; NOLAN, BRIAN (ESRI)
This report monitors the evolution of poverty in Ireland from 2004 to 2007. This period marks the end of the first ten year National Anti?Poverty Strategy (NAPS) in Ireland which ran from 1997 to 2007, and marks the beginning of the National Action Plan for Social Inclusion 2007 to 2016. The results therefore provide an important benchmark for the new programme as well as providing an insight into the changes in the level and distribution of poverty that occurred during the final stages of the NAPS. T Introduction We know now that this period was the final stage of the economic boom in Ireland, which saw dramatic growth in employment levels and in national income. Signs of an economic downturn began to emerge in early 2008 and Ireland entered recession in mid?2008. The return of high unemployment rates, falling income levels and cuts in public expenditure all bring renewed challenges to eliminating poverty, however it is clear from the results outlined in this report that poverty was a very real issue for many Irish households even at the height of the economic boom. The study identifies the groups who were vulnerable at the onset of the economic crisis. The analyses highlight the longer?term social processes that underlie poverty risks, such as low educational attainment, social background, ill health and disability, household composition (e.g. lone parenthood) and exclusion from the labour market. These processes and risk factors are likely to be affected by the recession, but are not determined by the economic cycle. The dramatic rise and fall in the economy also has implications for the measurement of poverty, pointing to the need for measures adopted to be able to provide a valid and reliable estimate of poverty within a changing context. It has been consistently argued in an extensive body of ESRI research on poverty that a multidimensional approach to measuring poverty, which does not rely solely on income, is essential. The structure of the report reflects the life?cycle approach as framed by the Developmental Welfare State report published by the National Economic and Social Council (NESC) in 2005. It focuses on three life?cycle groups: children, adults of working age and older people. Poverty is measured in a multi?dimensional way by taking into account both relative income poverty and non?monetary indicators of deprivation. This combination of measures taps into the extent to which individuals are excluded from the normal way of life and standard of living in society.
PUBLISHED
Keywords: Social Policy; Poverty